Challenges of e-procurement: a case study of JICA assisted Northern Bangladesh Integrated Development Project (NOBIDEP) under Local Government Engineering Department (LGED). - Sayed, Md. Abu (BRAC Univeristy, 2017)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2016.